Perceptions and Evaluations of Incivility in Public Online Discussions—Insights From Focus Groups With Different Online Actors - Bormann, Marike (Frontiers in Political Science, 2022)
Incivility in public online discussions has received much scholarly attention in recent years. Still, there is controversy regarding what exactly constitutes incivility and hardly any study has examined in depth what different participants of online discussions perceive as uncivil. Building on a new theoretical approach to incivility as a violation of communication norms, this study aims to close this research gap: In five heterogenous focus groups, different types of actors in online discussions, namely community managers, users, and members of online activist groups, discussed what they perceive as norm-violating and how these violations differ in terms of severity. Results suggest that incivility is a multidimensional construct and that the severity of different norm violations varies significantly. Although the actors share a relatively large common ground as to what they perceive as uncivil, several role-specific perceptions and individual evaluation criteria become apparent. Based on the results, a differentiated typology of perceived incivility in public online discussions is developed.